TESTING RESEARCH OF STRESS AND DEFORMATION OF WELDED STRUCTURE BODY - WEI DongHai; LI KeRui; DU Bing; CHENG Peng (Jixie qiangdu)
The initial residual stress and deformation of welded body was measured respectively with blind-hole method and digital level. The test of residual stress after vibration aging,thermal aging and shot peening and the test of deformation after processing were done. The results show that the initial residual stress of welded body can reach up to 300. 6 MPa. The maximum deformation of the guide rails is 2882. 07 μm,which means obvious deformation. After complex aging process,the maximum residual stress of two welded bodys respectively is reduced to 43. 8 MPa and 12. 1 MPa,which both below 50 MPa. After processing,the maximum straightness of the guide rail respectively is 26. 7 μm and 25. 4 μm,which is significantly reduced.